'Finding another Face inside my Face’: The Semiotics of Mime in Edgar Nkosi White's Racialized Dramaturgies” - Casado Gual, Núria (Miscelánea: A Journal of English and American Studies, 2008)
According to Tadeusz Kowzan, facial mime may be regarded as the system of kinetic signs that is closest to verbal expression. At the same time, as Kowzan contends, mime constitutes —together with gesture— the most personal and individualized expressive mode in the theatre, submitted as it is to the performer’s physical, psychological and actoral idiosyncrasies. In the dramatic production of the Afro-Caribbean playwright Edgar Nkosi White, mimic expression plays a prominent role: indeed, a broad variety of facial inscriptions informs both the dialogues and stage directions of his plays. Even if the mimic signs devised by the author have differentiated functions and do not exist in isolation, complementing as they do other verbal and non-verbal signs, most of them expose the inner and external tensions underlying situations of racial oppression. Considering the double axis of eye- and mouth-expression that determines facial gesturality, this essay intends to analyze the mimic expressivity of Edgar Nkosi White’s characters and its specific contribution to the author’s theatricalization of the phenomenon of racialism. At a more general level, the mimic designs inscribed in Edgar Nkosi White’s plays will be shown to unveil the discourse of ambivalence that tinges the racialized body when this is portrayed and represented from the victim’s point of view.
Keywords: Theatre semiotics; Afro-Caribbean theatre; African American theatre; Racism; Edgar Nkosi White